Prediction of stimulus-independent and task-unrelated thought from functional brain networks - Aaron Kucyi (Nature Portfolio, 2021)
People spend much of their daily lives thinking about things that are unrelated to their immediate environment. Using fMRI, Kucyi et al. show that occurrence of these “stimulus-independent” thoughts can be predicted from a complex pattern of coordinated activity between distinct parts of the brain.